Efeito esquistossomicida in vitro e in vivo do extrato das folhas de Passiflora edulis Sims associado ou não ao praziquantel - FRAZÃO, Gleycka Cristine Carvalho Gomes (2021)
Around 240 million people worldwide are infected by the helminth Schistosoma mansoni, representing a serious public health problem. Considered a neglected disease, the treatment of schistosomiasis is limited, with Praziquantel (PZQ), but side effects and parasite resistance have already been reported. This picture makes Research and Development of new alternative and/or complementary therapeutic agents necessary. In this sense, natural products, especially those of plant origin represent important sources of bioactive compounds, likely to cause synergistic effects with Praziquantel. Thus, the objective of this study was to evaluate the efficacy and safety of Passiflora edulis Sims. (vernacular name: passion fruit) as an alternative and/or therapeutic complement to praziquantel in the control of experimental schistosomiasis mansoni. P. edulis leaves were collected from cultivated areas, in Paço Lumiar, Maranhão, Brazil; submitted to standardized extraction by maceration in 70% ethanol in 1:8 hydromodule. Initially, in vitro tests of cytotoxicity (GM-0754 cell line and hemolytic activity) and efficacy (schistosomicide evaluation on adult worms viability and inhibition of oviposition) were performed with hydroethanolic extract of P. edulis leaves (EPE) at different concentrations. Subsequently, in vivo assays were performed using Swiss mice, divided into 05 groups (n: 06 animals/group): healthy control (non-infected and untreated animals); negative control (infected animals without treatment); positive control (infected animals treated with PZQ 50mg/Kg), EPE group (infected animals treated with hydroethanolic extract of P. edulis 50mg/Kg) and EPE+PZQ group (infected animals treated with hydroethanolic extract of P. edulis leaves 50mg/Kg in association with Praziquantel 50mg/Kg); the animals were infected with 50 cercariae of S. mansoni on day 0, treated from day 45 to 51 after infection and euthanized on day 90 post-infection. The results showed no cytotoxic at any tested dose of EPE. EPE showed significant schistosomicidal activity and oviposition inhibition in in vitro tests. In the in vivo assays EPE reduced the number of eggs in feces as well as those retained in liver and intestinal tissues. EPE also reduced the extent of liver granulomas. This effect was enhanced when EPE was associated with PQZ. Based on the date obtained, it can be concluded that EPE, both when used alone and in association with PZQ, has an antischistosomicidal effect, contributing to a decrease in the elimination of eggs in the feces and thus reducing the spread of the diasease.